Lesotho : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This Joint Staff Assessment examines the Poverty Reduction Strategy Paper (PRSP) Progress Report for Lesotho. Poverty monitoring and the medium-term macroeconomic framework are areas in which the government has made considerable progress. The government has taken a number of steps to ensure that the PRSP will be completed and presented to the IMF and World Bank by November 2003. The report indicates that the government and participating donors have guaranteed sufficient funds to complete the PRSP.